Utilization of Plastic Waste in Sarirejo Village Ngaringan District Grobogan Regency - Itok Dwi Kurniawan; Alfin Septian Pradana; Daffa Luviansyah; Eugenia Ivana Kasatyo; Febriana Endah Permatasari; Kameswari Dyah Tungga Dewi; Indah Kusuma Ningsih; Ricca Padyansari; Yunita Pratika Sari; Nur’aini Kusuma Puteri (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2022)
This community service activity aims to empower and improve the skills of the Sarirejo Village community through the activities of Pemberdayaan dan Kesejahteraan Keluarga (PKK) women in Sarirejo Village and elementary school students in Sarirejo Village in utilizing plastic waste into ecobricks for mothers. Vertical garden and piggy bank for elementary school students, as well as fashion show competition for Galsari Hamlet residents. Community service activities were carried out by counseling methods for PKK Sarirejo Village women, Sarirejo Village Elementary School students, and Galsari Hamlet residents regarding the importance of using and processing plastic waste, the practice of using plastic waste into ecobricks, vertical gardens, piggy banks, and costumes. In carrying out activities, mentoring and evaluation of activities are carried out. The participation and enthusiasm of PKK women in making ecobricks as well as Sarirejo Village Elementary School students and Galsari Hamlet residents in activities were very good and actively contributed to counseling and plastic waste processing practices. The impact of this community service activity was able to increase public awareness regarding the importance of processing plastic waste in Sarirejo Village into ecobricks, vertical gardens, piggy banks, and costumes. This community service activity is expected to continue and benefit the people of Sarirejo Village.